Dissected identity: The poetic anatomies of Mizrahi women (Part II) - Tsoffar, Ruth (Hagar: Studies in Society and Culture, 2007)
The poetic construction of ethnic anatomies is based on references to the internal and external body in the work of Mizrahi poets, including Erez Bitton, Roni Someck, Eli Bachar, Peretz Dror-Banai, Shelly Elkayam and Miri Ben Simhon. The imaginary composite body that emerges piecemeal from this poetry constitutes a map that locates the contested zones of ethnicity and gender and the terrain on which cultural differences are played out. Such a composite portrait accentuates the fragmentary, isolated, dismembered and colonized situation of the Israeli ethnic and gendered body. Shelly Elkayam, for example, situates the female body in a time and place free from the overdetermined influence of the canon, ideology and intertextuality, thereby creating a female ontological presence that manifests an autonomous gendered identity. By plotting a local woman ’s face with pockmarks and scars, Miri Ben Simhon turns it into a topographical palimpsest of contested experiential and geographical histories.